2008
DOI: 10.1007/s11671-008-9140-6
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Nanoparticles Synthesis and Characterization from H2S Gas, Using Novel Biodegradable Iron Chelates in W/O Microemulsion

Abstract: Sulfur nanoparticles were synthesized from hazardous H2S gas using novel biodegradable iron chelates in w/o microemulsion system. Fe3+–malic acid chelate (0.05 M aqueous solution) was studied in w/o microemulsion containing cyclohexane, Triton X-100 andn-hexanol as oil phase, surfactant, co-surfactant, respectively, for catalytic oxidation of H2S gas at ambient conditions of temperature, pressure, and neutral pH. The structural features of sulfur nanoparticles have been characterized by X-ray diffraction (XRD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 21 publications
3
53
1
Order By: Relevance
“…[18,19]. Some recent studies [1,[3][4][5][6][7] have reported the novel applications of sulfur nanoparticles, and subsequently researchers are also exploring the novel synthesis routes [8,[11][12][13][14][15]. In our previous study, we also have reported an easy route for generation of sulfur nanoparticles in aqueous surfactant media [11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[18,19]. Some recent studies [1,[3][4][5][6][7] have reported the novel applications of sulfur nanoparticles, and subsequently researchers are also exploring the novel synthesis routes [8,[11][12][13][14][15]. In our previous study, we also have reported an easy route for generation of sulfur nanoparticles in aqueous surfactant media [11].…”
Section: Introductionmentioning
confidence: 97%
“…Colloidal or nano sized sulfur particles were synthesized by different routes such as acid hydrolysis of sodium thiosulphate [8][9][10][11], polysulfide decomposition [12,13], H 2 S reduction by Fe-chelate [14], ultrasonic treatment of sulfur-cystine solution [15]. In our previous study, the advantages and disadvantages of different synthesis methods were discussed to justify the need of an aqueous based easy synthesis route of sulfur nanoparticles synthesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite many exciting applications, there are only a few recent literatures available on synthesis of sulfur nanoparticles by different investigators [9][10][11][12] in both aqueous and microemulsion phase by different routes. Deshpande et al [9] have synthesized sulfur nanoparticles from H 2 S gas by using biodegradable iron chelate catalyst in reverse microemulsion technique.…”
Section: Introductionmentioning
confidence: 99%
“…Deshpande et al [9] have synthesized sulfur nanoparticles from H 2 S gas by using biodegradable iron chelate catalyst in reverse microemulsion technique. They found a-sulfur or rhombic sulfur of average particle size 10 nm with a particle size range of 5-15 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation